Valorization of melon fruit (Cucumis melo L.) by-products: phytochemical and biofunctional properties with emphasis on recent trends and advances - Gómez-García, Ricardo (2021)
Background: For modern food industry, sustainability of food processing is a major concern coupled to the reduction of waste generation. Fruit and vegetable processing require of modernization to valorize the waste and by-products highly generated, particularly because they are rich in natural beneficial components which are demanded to human health. Melon (Cucumis melo L.) processing generate a high amount of peels and seeds, which are recognized with higher content of bioactive compounds than pulp, including polyphenols, carotenoids and oils. Scope and approach: In this review, we summarize information about of the bioactive compounds present in the melon fruit, together with the nutritionals properties that it presents as a functional food, with a focus on its by-products (pulp, seed and peel). The melon fruit contains important bioactive compounds, mainly the peel has a high content of antioxidants which are of interest in the food, cosmetic and pharmaceutical industries. These findings pretend to support new research concerning the formulation of novel functional foods based on melon by-products. Key finding and conclusions: Extracts of melon fruit, mainly from the peel, have been shown to possess phytochemical compounds that exhibit antioxidant, antimicrobial, antidiabetic, antiviral, anti-inflammatory, anti-hypoglycemia and anti-proliferative effects in various in vitro and in vivo test. However, it is necessary for further analyze the nutritional and functional potential of these by-products, the therapeutic and clinic mechanisms involved and to develop its industrial process as functional or nutraceutical food products.